Ultrahigh-strength 6-series aluminum alloy profile for automobile structural parts and preparation method of ultrahigh-strength 6-series aluminum alloy profile

By optimizing the composition and heat treatment process of the 6-series aluminum alloy profile, the problem of insufficient resistance to deformation and cracking under high yield strength is solved, and the high yield strength and good resistance to deformation and cracking of the material are achieved. It is suitable for automotive structural parts High security and lightweight requirements.

CN119433305APending Publication Date: 2025-02-14NINGBO XINTAI MACHINERY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411541325.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

It is difficult for existing 6-series aluminum alloy profiles to maintain good resistance to deformation and cracking under high yield strength, especially in automotive structural parts, which are difficult to meet stricter safety and lightweight requirements.

Method used

By optimizing the composition of aluminum alloy profiles, including the content and distribution of elements such as Mg, Si, Cu, Mn, Cr, etc., a sandwich structure of "coarse crystal layer/fiber structure/coarse crystal layer" is adopted, and a specific heat treatment process is used. Such as homogenization treatment, preheating, quenching and aging treatment, it can improve the strengthening effect of the material and resist deformation and cracking.

Benefits of technology

The yield strength of the aluminum alloy profile reached ≥360Mpa, and the downward displacement reached more than 200mm in the three-point bending test without breaking, which significantly improved the material's resistance to deformation and cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433305A_ABST
    Figure CN119433305A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of aluminum alloy extruded profiles, and relates to an ultrahigh-strength 6-series aluminum alloy profile for an automobile structural part and a preparation method of the ultrahigh-strength 6-series aluminum alloy profile. According to the method, the strengthening effect of the aluminum alloy profile is optimized through the constraint of the relative relation of the Mg content and the Si content, deep mastering of the relation between the elements and reasonable selection and control of the adding amount of the alloy elements, and especially in the peak aging state, the performance of the material in a bending test is improved by avoiding Si excess and reducing the risk of grain boundary embrittlement; by regulating and controlling the size of the dispersion particles and optimizing the microstructure, comprehensive optimization of deformation cracking resistance, surface quality and extrudability is achieved, the yield strength of the prepared aluminum alloy profile is larger than or equal to 360 Mpa, the pressing displacement can reach 200 mm without breakage, and after further optimization, the aluminum alloy profile does not break when the pressing displacement is larger than 320 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloy extruded profiles, and relates to an ultra-high-strength 6-series aluminum alloy profile for automobile structural parts and a preparation method thereof. Background Art

[0002] Due to its unique properties, 6-series aluminum alloys are increasingly used in the automotive industry, especially in the context of lightweight design. 6-series aluminum alloys are lighter than traditional steels and can significantly reduce the overall weight of the vehicle, thereby improving fuel efficiency or extending the range of electric vehicles. 6-series aluminum alloys have good extrusion properties, allowing them to be made into complex shapes and suitable for manufacturing various structural parts of automobiles. Through appropriate heat treatment processes, the strength and hardness of the material can be further improved to meet the design requirements of different components. With the growing demand for lightweight vehicles, the application of 6-series aluminum alloys is also expanding. In order to achieve a higher lightweight effect, not only does the material itself need to be light enough, but it also requires sufficient strength to reduce the size of the parts while maintaining safety, thereby reducing weight.

[0003] It can be applied to various parts of automobiles, especially functional structural parts, such as front beams, longitudinal beams, anti-collision bars, battery boxes and other parts. These parts need to have good deformation and crack resistance in order to effectively protect people's safety in collisions. At present, most 6 series aluminum profiles can only guarantee their good deformation and crack resistance at low strength levels. It is of great practical significance to improve the good deformation and crack resistance of profiles under ultra-high strength. At present, there are few reports on 6 series aluminum alloys with high deformation and crack resistance under yield strength>360MPa.

[0004] As the automotive industry continues to increase its requirements for lightweight and safety, the development of 6-series aluminum alloy materials with high strength and good resistance to deformation and cracking has become a research hotspot. This will not only help automakers meet more stringent environmental regulations in the future, but also improve the overall performance and safety of vehicles. Summary of the invention

[0005] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and to propose an ultra-high strength 6 series aluminum alloy profile for automobile structural parts, whose yield strength is ≥360Mpa. When used in automobile anti-collision beams, the impact downward displacement in a three-point bending test can reach 200mm without breaking.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] An ultra-high strength 6-series aluminum alloy profile for automobile structural parts. The aluminum alloy profile raw material is composed of the following elements in percentage by mass: 0.80-1.2% Mg, 0.75-1.1% Si, 0.35-0.60% Cu, 0.30-0.70% Mn, 0.10-0.20% Cr, 0-0.25% Fe, and the rest is Al and unavoidable impurities.

[0008] Preferably, the aluminum alloy profile raw material is composed of the following elements in percentage by mass: 0.80-1.2% Mg, 0.75-1.1% Si, 0.40-0.50% Cu, 0.30-0.70% Mn, 0.10-0.20% Cr, 0-0.25% Fe, and the rest is Al and unavoidable impurities.

[0009] In the above-mentioned ultra-high strength 6 series aluminum alloy profiles for automotive structural parts, as an optimization, the contents of Mg, Si, Mn, Fe, and Cr meet the following conditions:

[0010] 1.9%≤Mg+Si free +Cu≤2.4%, 0.40%≤Mg-0.71Si free ≤0.60%,

[0011] Among them, Si free =Si-0.34Mn-0.25Fe-0.18Cr.

[0012] In the above-mentioned ultra-high strength 6 series aluminum alloy profiles for automobile structural parts, as an optimization, the average size of the dispersed particles of Mn and Cr in the aluminum alloy profile is ≤0.1um.

[0013] In the above-mentioned ultra-high strength 6 series aluminum alloy profiles for automotive structural parts, as an optimization, the aluminum alloy profile has a sandwich structure of "coarse grain layer / fibrous structure / coarse grain layer", and the total thickness of the coarse grain layers on both sides is ≤0.2×wall thickness.

[0014] In the above-mentioned ultra-high strength 6 series aluminum alloy profiles for automotive structural parts, as an optimization, the contents of Mn and Cr must meet the following conditions:

[0015] 0.40%≤Mn+Cr≤0.55%.

[0016] The present invention also provides a method for preparing the ultra-high strength 6-series aluminum alloy profile for automobile structural parts, the method comprising the following steps:

[0017] S1. Prepare raw materials;

[0018] S2, melting the raw materials into cast aluminum bars, and then homogenizing them;

[0019] S3, then preheating the aluminum rod, and then using a hot extrusion splitter die to produce an extruded cavity profile;

[0020] S4. Quench the extruded cavity profile and perform aging treatment after cooling to room temperature.

[0021] In the above-mentioned method for preparing ultra-high strength 6 series aluminum alloy profiles for automotive structural parts, the homogenization treatment temperature is 400-530°C, the time is 0.5-24h, and after the homogenization treatment, the aluminum rod is cooled to room temperature at a cooling rate of >250°C / h.

[0022] In the above-mentioned method for preparing ultra-high strength 6-series aluminum alloy profiles for automobile structural parts, the preheating temperature is 520-560°C.

[0023] In the above-mentioned method for preparing ultra-high strength 6-series aluminum alloy profiles for automobile structural parts, the quenching temperature is 490-550°C.

[0024] In the above-mentioned method for preparing ultra-high strength 6-series aluminum alloy profiles for automobile structural parts, the aging temperature is 160-185° C. and the aging time is 3-15 hours.

[0025] Compared with the prior art, the present invention has the following beneficial effects: the present invention optimizes the strengthening effect of aluminum alloy profiles by constraining the relative relationship between Mg and Si contents and profoundly grasping the relationship between each element, rationally selecting and controlling the addition amount of alloying elements, and especially in the peak aging state, by avoiding excess Si, reducing the risk of grain boundary embrittlement and improving the performance of the material in the bending test; by regulating the size of dispersed particles and optimizing the microstructure, the comprehensive optimization of deformation crack resistance, surface quality and extrudability is achieved, the yield strength of the prepared aluminum alloy profile is ≥360Mpa, the downward displacement can reach 200mm without fracture, and after further optimization, the downward displacement is greater than 320mm without fracture. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is the thickness of the coarse-grained layer of the aluminum alloy profile prepared in Example 3;

[0027] Figure 2 is the thickness of the coarse-grained layer of the aluminum alloy profile prepared in Comparative Example 6;

[0028] Figure 3 The dispersed phase size of the aluminum alloy profile prepared in Example 3;

[0029] Figure 4 The dispersed phase size of the aluminum alloy profile prepared in Comparative Example 6;

[0030] Figure 5 The three-point bending test results of the aluminum alloy profile prepared in Example 3;

[0031] Figure 6 The three-point bending test results of the aluminum alloy profile prepared in Comparative Example 4 are shown. DETAILED DESCRIPTION

[0032] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0033] Mg and Si are the main additive elements of 6 series alloys. They interact and precipitate to form GP zone, β”, β ’ The second phase particles such as β phase strengthen the matrix. According to the latest research, the evolution law of precipitation phase in Al-Mg-Si alloy during aging is as follows:

[0034] Supersaturated solid solution → GP zone → β” → β ’ (B ’ , U1, U2)→β.

[0035] Among them, the β” phase has the best strengthening effect and is the main strengthening precipitation phase in the peak aging alloy; ’ The β phase is the main precipitation phase in the alloy when overaging is severe, and its strengthening effect is not as good as that of the β" phase; the β phase is an equilibrium phase, which is incoherent with the aluminum matrix, and its strengthening effect is limited.

[0036] Table 1: Information on precipitation phases in 6 series alloys

[0037] Precipitated phase Coherence relationship with matrix Chemical composition GP Area Coherence <![CDATA[Mg 2+X To the 7-X-Y Yeah 2+Y ]]> β” Coherence <![CDATA[Mg5Si6]]> β’ Semi-coherent <![CDATA[Mg5Si3]]> β Incoherent <![CDATA[Mg2Si]]>

[0038] In the present invention, the aging state of the 6xxx alloy is the peak aging state, and the main aging precipitation strengthening phase is the β" phase, wherein the Mg / Si mass ratio in the β" phase is 0.71. If Mg / Si>0.71, there will be a part of Mg without Si to form a β" phase, then Mg is in excess, otherwise, Si is in excess.

[0039] The strategy of excess Mg is adopted in the preferred embodiment of the present invention for the following reasons:

[0040] 1. If there is excess Si in the alloy, it is easy to segregate to the grain boundaries, causing grain boundary embrittlement, which is prone to cracks or even fractures during impact bending tests.

[0041] 2. Excess Mg in aluminum alloys is generally dissolved in the aluminum matrix. This state is conducive to improving the hardening index of aluminum alloys during deformation, thereby improving the uniform plastic deformation capacity of the material, thereby delaying the rapid fracture failure phenomenon caused by localized delayed plastic deformation.

[0042] However, too much excess Mg will deteriorate the extrudability of the material, which is not conducive to large-scale mass production. It is necessary to strictly control the excess Mg content, both to ensure a certain amount of excess Mg and to prevent too much excess. Therefore, after a lot of practice, the present invention stipulates the following conditions for the excess Mg content: 0.40% ≤ Mg-0.71Si free ≤0.60%.

[0043] Si is an important additive element for 6 series alloys. It mainly forms a β" phase with Mg and plays a strengthening role. However, Si is easy to combine with Fe, Mn, and Cr elements to form a second phase, resulting in a portion of Si being consumed in advance and thus unable to be used to form a β" phase with Mg. Therefore, Si is used in the preferred embodiment of the present invention. free To represent the Si content that can form the β" phase. Previously, the industry has not paid enough attention to this issue, and the industry has selectively ignored it. In recent years, some research institutions and a small number of industry practitioners have begun to roughly estimate Si based on experience. free In actual application, there is often a certain deviation. However, in the ultra-high strength alloy of the present invention, this problem cannot be ignored. A small deviation in the design of the alloy composition will be magnified, resulting in a waste of elements and failure to achieve the effect of the present invention. The present invention combines theoretical research calculations with practical verification to obtain the following results: free For a more accurate estimate, see the formula below and Table 2

[0044] Si free =Si-0.34Mn-0.25Fe-0.18Cr

[0045] Table 2: Second phases of compounds formed by Si and other elements

[0046] Second phase Specific composition Si consumption factor Formation Stage α-AlFeSi <![CDATA[Al8Fe2Si]]> 0.25 Casting α-AlMnSi <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 15 <h2 style=";text-align:left;direction:ltr"> Mn3Si2<h2 style=";text-align:left;direction:ltr"> 0.34 Homogenization τ-AlCrSi <![CDATA[Al9Cr3Si]]> 0.18 Homogenization

[0047] Cu is also the main added element in the 6 series aluminum alloy. Together with Mg and Si, it determines the strength level of the 6xxx aluminum alloy, and it mainly plays a role in supplementary strengthening. However, too high Cu content will deteriorate the intergranular corrosion performance of the material, while damaging the extrudability of the material and increasing quenching sensitivity. Therefore, in the present invention, Cu is controlled within a moderate range of 0.35-0.60%, which can be further optimized to Cu: 0.40-0.50%. At the same time, as the total content of Mg, Si, and Cu increases, the strength of the alloy increases, but the toughness will also decrease. Therefore, the present invention stipulates in the preferred embodiment: 1.9% ≤ Mg+Si free +Cu≤2.4%. Within this range, strength and toughness can be optimally balanced.

[0048] The added elements Mn and Cr exist in the aluminum alloy in the form of submicron dispersed phase particles. These dispersed phase particles have the effect of hindering recrystallization. Their ability to hinder recrystallization is closely related to the size and number of dispersed phase particles. The smaller the size and the greater the number, the stronger the ability to hinder recrystallization. In aluminum extrusion, recrystallization often occurs on the surface of the profile to form a relatively coarse surface coarse crystal layer structure, which has a serious negative impact on the deformation cracking, corrosion, surface quality, etc. of the profile product. Therefore, adding Mn, Cr and other elements that inhibit recrystallization has a significant effect on reducing and eliminating the surface coarse crystal layer and improving product performance. In the present invention, Mn and Cr elements are mainly added. If the addition amount is too little, the ability to hinder recrystallization is insufficient, and the surface coarse crystal layer is too thick. If the addition amount is too much, the extrusion pressure is large, which is not conducive to production. The present invention stipulates Mn: 0.30-0.70%; Cr: 0.10-0.20%, which can be further optimized to Mn+Cr: 0.40~0.55%.

[0049] Embodiment 1-10:

[0050] S1. The aluminum alloy profile compositions of Examples 1-10 are configured as shown in Table 1;

[0051] S2, adding the prepared alloy raw materials into a smelting furnace for smelting at 780°C to melt them all into liquid to form aluminum melt, and then keeping the temperature for about half an hour to remove slag and refine the aluminum melt after all the melts are melted into liquid; after the components are adjusted to meet the requirements, lowering the temperature of the aluminum melt to 720°C, and sequentially performing standing, slagging and casting to obtain a round cast rod, and then performing homogenization treatment at a homogenization temperature of 460°C for 6 hours, and cooling the aluminum rod to room temperature at a cooling rate of 300°C / h after homogenization;

[0052] S3, then the aluminum rod is preheated at 550°C, and then a hot extrusion die is used to obtain an extruded profile;

[0053] S4, then the extruded profile is quenched at 500°C, cooled to room temperature at 8°C / s, and finally the extruded profile is aged at 165°C for 10h.

[0054] Comparative Examples 1-6:

[0055] S1. The aluminum alloy profile compositions of Comparative Examples 1-6 are configured as shown in Table 1;

[0056] S2, adding the prepared alloy raw materials into a smelting furnace for smelting at 780°C to melt them all into liquid to form aluminum melt, and then keeping the temperature for about half an hour to remove slag and refine the aluminum melt after all the melts are melted into liquid; after the components are adjusted to meet the requirements, lowering the temperature of the aluminum melt to 720°C, and sequentially performing standing, slagging and casting to obtain a round cast rod, and then performing homogenization treatment at a homogenization temperature of 460°C for 6 hours, and cooling the aluminum rod to room temperature at a cooling rate of 300°C / h after homogenization;

[0057] S3, then the aluminum rod is preheated at 550°C, and then a hot extrusion die is used to obtain an extruded profile;

[0058] S4, then the extruded profile is quenched at 500°C, cooled to room temperature at 8°C / s, and finally the extruded profile is aged at 165°C for 10h.

[0059] Three-point bending test method: According to the three-point bending test method in the national standard GB / T 33910-2017 "Aluminum and aluminum alloy extruded profiles for automobiles", the specific experimental parameters are as follows: span L = 920mm, pressure head radius R = 127mm, pressing speed V = 2mm / s. Evaluation standard: When the pressing distance is 200mm, the profile does not break.

[0060] Table 3: Elemental composition of aluminum alloy profiles prepared in Examples 1-10 and Comparative Examples 1-6

[0061]

[0062] Table 4: Performance test results of aluminum alloy profiles prepared in Examples 1-10 and Comparative Examples 1-6

[0063]

[0064]

[0065] The profiles produced in Examples 1-10 adopt the scheme provided by the present invention, and can achieve the effects of the present invention as shown in Tables 2 and 3. Among them, the alloy composition of Example 1-7 is further optimized, and its mechanical properties and three-point bending have reached a relatively high level, and the comprehensive performance is the best.

[0066] from Figure 1 , 3 , 5 It can be seen that the contents of the main alloying elements such as Mg, Si, Cu, Mn, Cr, the coarse-grained layer and the dispersed phase particles of the aluminum alloy profile in Example 3 of the present invention are all within the optimization range required by the present invention, which not only ensures that the material has good mechanical properties (such as higher Rp 0.2Yield strength), and also ensured that the material performed very well in the three-point bending test, not only did it not break, but no cracks were found. Figure 2 , 4 It can be seen that the contents of the main alloying elements such as Mg, Si, Cu, Mn, and Cr in Comparative Example 6 are within the required range of the present invention, which is the same as that in Example 3, but the coarse-grained layer is thicker and the dispersed phase particle size is larger. 0.2 The values ​​and three-point bending properties can achieve the effects of the present invention, but the three-point bending performance is slightly worse than that of Example 3, indicating that effective control of the coarse-grained layer and dispersed phase particles can further improve its toughness.

[0067] The Si and Cu contents in Comparative Examples 1 and 2 are respectively lower than the ranges set by the present invention, which results in poor mechanical properties of the materials, especially Rp 0.2 The value is relatively low. This indicates that the insufficient alloying element content cannot provide sufficient strengthening effect, affecting the overall performance of the material.

[0068] The Si content in Comparative Example 3 exceeds the range set by the present invention. Although the mechanical properties are relatively high, the three-point bending performance is poor, and fracture occurs before the downward displacement reaches 200 mm.

[0069] from Figure 6 It can be seen that the Mn and Cr contents in Comparative Examples 4 and 5 are respectively lower than the range set by the present invention, resulting in a coarsening of the coarse-grained layer thickness, which in turn causes poor toughness of the material and failure in the three-point bending test.

[0070] In summary, the present invention successfully prepared aluminum alloy profiles with excellent mechanical properties and good processing properties by precisely controlling the contents of key elements such as Mg, Si, Cu, Mn, Cr, etc. These results not only verify the effectiveness of the present invention, but also provide an important reference for the design and application of aluminum alloy materials.

[0071] The parts of the embodiments herein that are not exhaustive of the midpoint values ​​of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.

[0072] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.

[0073] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. An ultra-high strength 6 series aluminum alloy profile for automotive structural parts, characterized in that: The aluminum alloy profile raw material is composed of the following elements in percentage by mass: 0.80-1.2% Mg, 0.75-1.1% Si, 0.35-0.60% Cu, 0.30-0.70% Mn, 0.10-0.20% Cr, 0-0.25% Fe, and the rest is Al and unavoidable impurities.

2. The ultra-high strength 6-series aluminum alloy profile for automobile structural parts according to claim 1, characterized in that: The contents of Mg, Si, Cu, Mn, Fe and Cr must meet the following conditions: 1.9%≤Mg+Si free +Cu≤2.4%,0.40%≤Mg-0.71Sifree≤0.60%, Among them, Si free =Si-0.34Mn-0.25Fe-0.18Cr.

3. The ultra-high strength 6 series aluminum alloy profile for automobile structural parts according to claim 1 or 2, characterized in that: The average size of dispersed particles of Mn and Cr in aluminum alloy profiles is ≤0.1um.

4. The ultra-high strength 6-series aluminum alloy profile for automobile structural parts according to claim 1 or 2, characterized in that: The aluminum alloy profile has a sandwich structure of "coarse grain layer / fibrous structure / coarse grain layer", and the total thickness of the coarse grain layers on both sides is ≤0.2×wall thickness.

5. The ultra-high strength 6 series aluminum alloy profile for automobile structural parts according to claim 1 or 2, characterized in that: The contents of Mn and Cr must meet the following conditions: 0.40%≤Mn+Cr≤0.55%.

6. A method for preparing an ultra-high strength 6-series aluminum alloy profile for automobile structural parts as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: S1. Prepare raw materials; S2, melting the raw materials into cast aluminum bars, and then homogenizing them; S3, then preheating the aluminum rod, and then using a hot extrusion splitter die to produce an extruded cavity profile; S4. Quench the extruded cavity profile and perform aging treatment after cooling to room temperature.

7. The method for preparing ultra-high strength 6-series aluminum alloy profiles for automobile structural parts according to claim 6, characterized in that: The homogenization temperature is 400-530° C., the time is 0.5-24 h, and after the homogenization, the aluminum rod is cooled to room temperature at a cooling rate of more than 250° C. / h.

8. The method for preparing ultra-high strength 6-series aluminum alloy profiles for automobile structural parts according to claim 6, characterized in that: The preheating temperature is 520-560℃.

9. The method for preparing an ultra-high strength 6-series aluminum alloy profile for automobile structural parts according to claim 6, characterized in that: The quenching temperature is 490-550℃.

10. The method for preparing ultra-high strength 6-series aluminum alloy profiles for automobile structural parts according to claim 6, characterized in that: The aging temperature is 160-185℃ and the time is 3-15h.